A review on various optical fibre sensing methods for batteries. (October 2021) - Han, Gaoce; Yan, Jize; Guo, Zhen; Greenwood, David; Marco, James; Yu, Yifei
Abstract: Batteries have rapidly evolved and are widely applied in both stationary and transport applications. The safe and reliable operation is of vital importance to all types of batteries, herein an effective battery sensing system with high performance and easy implementation is critically needed. This also requires the sensing system to monitor the states of batteries in real time. Among the available methods, optical fibre sensors have shown a significant advantage due to their advanced capabilities of which include the fast measurement of multiple parameters with high sensitivity, working without interfering the battery performance, being able to be composited in multiplexed configurations and being robust to various harsh environment conditions. This paper mainly discusses the current optical fibre sensing methods for batteries in terms of the working principles and critical reviews the sensing performance corresponding to different sensing parameters. Moreover, the challenges and outlooks for future research on battery sensing are derived. Highlights: Presents a critical review of all the main optical fibre sensing methods for batteries for the first time. Discusses the working principles of various optical fibre sensing methods systematically. Reviews the current developments of battery sensing in terms of different parameters. Reveals the challenges and the outlooks for the battery sensing system.